2018
DOI: 10.1177/0361684318777722
|View full text |Cite
|
Sign up to set email alerts
|

How Do Feminist-Identified Women Cope With Discrimination? A Feminist Standpoint and Grounded Theory Study

Abstract: Women experience a higher incidence of mental health concerns compared to men, and scholars have located these challenges within a discriminatory sociocultural context. Although scholars have suggested that feminist attitudes may shield women from discrimination, research on the protective role of feminist attitudes is discrepant and suggests that there are distinct differences between those who do and do not self-identify as feminist; namely, self-identifiers may be more protected in the face of discriminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…Consistent with previous findings (Padmanabhanunni & Edwards, 2016), participants in our study spoke about how activism provided them with the information and language to understand and label their experience as assault and to contextualize rather than internalize oppression. This finding is similar to Watson and colleagues’ (2018) finding that feminist women also used externalization to cope with their experiences of sexist discrimination. In this context, survivors highlighted the empowering shift they experienced in regard to their perceptions of themselves, others, and the world.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with previous findings (Padmanabhanunni & Edwards, 2016), participants in our study spoke about how activism provided them with the information and language to understand and label their experience as assault and to contextualize rather than internalize oppression. This finding is similar to Watson and colleagues’ (2018) finding that feminist women also used externalization to cope with their experiences of sexist discrimination. In this context, survivors highlighted the empowering shift they experienced in regard to their perceptions of themselves, others, and the world.…”
Section: Discussionsupporting
confidence: 84%
“…It is noteworthy that in prior studies, women’s critical consciousness was linked with greater subjective well-being when operationalizations of critical consciousness included commitment to activism (e.g., Saunders & Kashubeck-West, 2006; Yoder et al, 2012), whereas women’s critical consciousness was linked with lower subjective well-being when operationalizations of critical consciousness did not include commitment to activism (e.g., Fischer & Good, 2004; Yoder et al, 2012). Our separate analysis of critical consciousness and feminist collective action in the present study helps to clarify this pattern and expand on prior conceptualizations of critical consciousness as simultaneously promoting subjective well-being and distress (e.g., Hercus, 1999; Moradi, 2012; Watson et al, 2018). This is an important nuance to consider for theory and practice.…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, distress, discontent, and anger are conceptualized as functional responses to recognizing oppression (e.g., Hercus, 1999; Moradi, 2012). Consistent with this conceptualization, in a qualitative study with primarily White, heterosexual and sexual minority, feminist-identified women, participants reported that feminist consciousness fostered their sense of self-worth, empowerment, and commitment to action, while at the same time promoting distress from greater awareness of oppression (Watson, Flores, et al, 2018). Moreover, nascent feminist critical consciousness without collective action (i.e., revelation feminist identity attitudes) has been linked to greater anger, psychological distress, and lower well-being in samples of predominantly White or racially and ethnically diverse women (e.g., Fischer & Good, 2004; Saunders & Kashubeck-West, 2006; Yoder et al, 2012).…”
Section: Feminist and Critical Consciousness Theories And Women’s Welmentioning
confidence: 93%
“…In addition, there is empirical support for the protective role of strong, positive ethnic and gender identity in the association between discrimination and psychological well-being (e.g., Lee & Ahn, 2013). In a qualitative study of coping behaviors among a sample of predominantly white women, Watson et al (2018) found that womanist and feminist identity was described by participants as protective amidst experiencing discrimination. In some instances, this greater awareness of systems of oppression had a negative impact on psychological well-being.…”
Section: Aspects Of Black Women’s Identity As Moderatorsmentioning
confidence: 99%